Mouse molar morphogenesis revisited by three dimensional reconstruction. I. Analysis of initial stages of the first upper molar development revealed two transient buds - Peterková, R; Lesot, H; Vonesch, J L; Peterka, M; Ruch, J V (The International journal of developmental biology, 1996)
Early stages of tooth development in the maxillary cheek region in the mouse were investigated by combined analysis of histological sections, computer assisted 3D reconstructions and morphometry. In ED 12.5 embryos, 3D reconstructions revealed an accessory epithelial bud (R1) and a large bud (R2), which appeared as a single bud-shaped epithelium in frontal sections. This developmentally most advanced dental epithelium in the mouse embryonic maxilla until ED 13.5, generally considered as the bud of the first molar, regressed during later development. Meanwhile the bud and cap of the first upper molar originated more posteriorly, from ED 13.5. The regression of R1 and R2 was associated with epithelial apoptosis. Apoptotic cells and bodies were apparent on sections in the R1 epithelium from ED 12.5. The R2 epithelium maintained the large bud-shaped appearance on sections, representing the largest part of the dental epithelium in the maxillary cheek region until ED 14.0; apoptoses were detected there as late as from ED 13.5. During regression, the R2 rudiment was transformed into the medial and lateral epithelial ridges, posteriorly in continuity with the arising cap of the first molar. The reduced R1 epithelium seemed to contribute to the medial ridge. These results should be taken into consideration in the interpretation of early odontogenesis in the upper jaw in the mouse. The interesting problem of the identification of tooth homology of the rudiments should be elucidated by further comparative morphological and paleontological investigations.
Keywords: histocytochemie; Histocytochemistry; Morphogenesis; Odontogenesis; Molar; morfogeneze; buněčná diferenciace; Microscopy; Image Processing, Computer-Assisted; Embryonic and Fetal Development; počítačové zpracování obrazu; Animals; mikroskopie; moláry; odontogeneze; zvířata; myši; Mice; embryonální a fetální vývoj; Cell Differentiation